Maternal, fetal and neonatal outcomes among pregnant women receiving COVID-19 vaccination: The preg-co-vax study - Mascolo, Annamaria; di Mauro, Gabriella; Fraenza, Federica; Gaio, Mario; Zinzi, Alessia; Pentella, Ciro; Rossi, Francesco; Capuano, Annalisa; Sportiello, Liberata (Frontiers in Immunology, 2022)
Introduction Although the European Medicine Agency (EMA) encourage Covid-19 vaccination in pregnant women, the scientific evidence supporting the use of Covid-19 vaccines during pregnancy is still limited. Aim We aimed to investigate adverse events following immunization (AEFI) with Covid-19 vaccines during pregnancy. Methods We retrieved Individual Case Safety Reports (ICSRs) related to the use of Covid-19 vaccines during pregnancy from the EudraVigilance database for the year 2021. We analyzed AEFI related to the mother and fetus/newborn. The reporting odds ratio (ROR) was computed to compare the reporting probability of spontaneous abortion between Covid-19 vaccines. Results During the study period, among 1,315,315 ICSRs related to Covid-19 vaccines, we retrieved 3,252 (0.25%) reports related to the use in pregnancy. More than half (58.24%) of ICSRs were submitted by non-health care professionals. Although the majority (87.82%) of ICSRs concerned serious AEFI, their outcomes were mostly favorable. The 85.0% of total ICSRs referred to pregnant women (n=2,764) while the 7.9% to fetuses/newborns (n=258). We identified 16,569 AEFI. The 55.16% were AEFI not related to pregnancy (mostly headache, pyrexia and fatigue),while the 17.92% were pregnancy-, newborn-, or fetus-related AEFI. Among pregnancy-related AEFI, the most reported was spontaneous abortion. mRNA vaccines had a lower reporting probability of spontaneous abortion than Viral Vector-Based vaccines (ROR 0.80, 95% CI 0.69–0.93). Moderna and Oxford-AstraZeneca vaccines had a higher reporting probability of spontaneous abortion (ROR 1.2, 95% CI 1.05–1.38; and ROR 1.26, 95% CI 1.08–1.47, respectively), while a lower reporting probability was found for Pfizer-BioNTech vaccine compared with all other Covid-19 vaccines (ROR 0.73, 95% CI 0.64–0.84). The 5.8% of ICSRs reported a fatal outcome. Conclusions No strong insight of unknown AEFI associated with Covid-19 vaccination in pregnant women was observed. Considering the high risk associated with SARS-CoV-2 infection, our analysis suggests that the benefits of Covid-19 vaccines during pregnancy outweigh the possible risks. However, it is important to continue monitoring the safety profile of Covid-19 vaccines in this subpopulation.